Untargeted metabolomic profiling of serum from dogs with chronic hepatic disease. (20th March 2019) - Lawrence, Yuri A.; Bishop, Micah A.; Honneffer, Julia B.; Cook, Audrey K.; Rodrigues‐Hoffmann, Aline; Steiner, Jörg M.; Suchodolski, Jan S.; Lidbury, Jonathan A.
Abstract: Background: Chronic hepatopathies present a diagnostic challenge, with different diseases being associated with similar clinical and laboratory findings. Characterization of dogs with chronic hepatopathies can be difficult and require costly diagnostic procedures such as acquisition of a liver biopsy specimen. Noninvasive and inexpensive biomarkers that reliably characterize chronic hepatopathies such as chronic hepatitis or a congenital portosystemic vascular anomaly may decrease the need for costly or invasive diagnostic testing and guide novel therapeutic interventions. Objective: To investigate differences in the serum metabolome among healthy dogs, dogs with congenital portosystemic shunts, and dogs with chronic hepatitis. Animals: Stored serum samples from 12 healthy dogs, 10 dogs with congenital portosystemic shunts, and 6 dogs with chronic hepatitis were analyzed. Methods: The serum metabolome was analyzed with an untargeted metabolomics approach using gas chromatography–quadrupole time of flight mass spectrometry. Results: Principal component analysis and heat dendrogram plots of the metabolomics data showed clustering among individuals in each group. Random forest analysis showed differences in the abundance of various metabolites including increased aromatic amino acids and xylitol in dogs with congenital portosystemic shunts. Based on the univariate statistics, 50 metabolites were significantly different among groups. Conclusions and Clinical Importance: The serum metabolome varies among healthy dogs, dogs with congenital portosystemic shunts, and dogs with chronic hepatitis. Statistical analysis identified several metabolites that differentiated healthy dogs from dogs with vascular or parenchymal liver disease. Further targeted assessment of these metabolites is needed to confirm their diagnostic reliability.